METODOLOGI LIFE CYCLE ASSESSMENT (LCA) UNTUK PEMILIHAN BAHAN DALAM PENGEMBANGAN PRODUK - MELFA YOLA (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2011)
The large consumption of electric and electronic equipment (EEE) causes many countries introduced the regulations regarding of sustainability aspect of product. This conditions forces the manufacturers to be more creative and inovative in designing the product and selecting materials for the product. This paper present a new methodology of Life Cycle Assessment (LCA) for material selection – a part of sustainable product design. The method used is Life Cycle Assessment which case study choosed is hair dryer. Data is analyzed by using Sima Pro 7.1 Software. It is expected that the methodology will give the steps of material selection for sustainable product design.  The Results will be analyzed from Characterization, Normalization and Single Score graph. Some alternatives materials will be suggested to replace current design, and the result shows that polypropylene and wood is better materials for environment. Keywords : Sustainable product design, Life Cycle Assessment (LCA)t, Methodology of Life Cycle Assessment, Material selection in sustainability, Hair Dryer